PENGARUH RETAIL MIX TERHADAP KEPUASAN PELANGGAN PADA FOODMART PRIMO LIPPO MALL KUTA - Hermawan, Adam; Mandala, Kastawan (E-Jurnal Manajemen, 2018)
A strategy that retail businesspeople can use to win the competition is by applying the right retail mix strategy . Elements of the retail mix can be combined and combined in such a way as to satisfy and retain existing customers. The purpose of this research is to explain the influence of retail mix simultaneously and partially to customer satisfaction at Foodmart Primo Lippo Mall Kuta. The research subjects were all Foodmart Primo Lippo Mall customers in Kuta, with a sample of 115 people . Determination of sample using purposive sampling method, that is sample determination technique with certain consideration. Data were analyzed using multiple linear regression analysis technique. The results showed that the retail mix (price, merchandise, promotion, service, store location, and store atmosphere) simultaneously and partially significant effect on customer satisfaction at Foodmart Primo Lippo Mall Kuta. This has the meaning that the better the application of the retail mix at Foodmart Primo Lippo Mall Kuta then the increase also the level of customer satisfaction.